Midwifery Care for Late Termination of Pregnancy: Integrative Review - Armour, S; Keedle, H; Gilkison, A; Dahlen, HG (Elsevier BV, 2023)
Midwives provide reproductive healthcare to women, including during termination of pregnancy (TOP) after 12 weeks (late TOP). Their expertise, knowledge and woman-centred care approach sees them ideally placed for this role. However, the medical, social and emotional complexities of late TOP can cause midwives significant distress. An integrative review methodology was used to examine the research on midwifery care for late TOP and identify support strategies and interventions available to midwives in this role. Five databases and reference lists were searched for relevant studies published between 2000 and 2021. A total of 2545 records were identified and 24 research studies included. Synthesis of research findings resulted in three themes: Positive aspects, negative aspects and carers need care. Midwives reported a high level of job satisfaction when caring for women during late TOP. Learning new skills and overcoming challenges were positive aspects of their work. Yet, midwives felt unprepared to deal with challenging aspects of late TOP care such as the grief and the psychological burden of the role. Caring for the baby with dignity had both positive and negative aspects. Midwives relied predominantly on close colleagues for help and debriefing as they felt poorly supported by management, judged by co-workers and lacked appropriate support to reduce the emotional effects of late TOP care. Midwives need support, although current evidence has not identified the most appropriate and effective strategy to support them in this role.
Keywords: Emotional support; Grief; Induced abortion; Midwifery care; Pregnancy termination; Supportive interventions; 32 Biomedical and Clinical Sciences; 4204 Midwifery; 4205 Nursing; 42 Health Sciences; 3215 Reproductive Medicine; Behavioral and Social Science; Reproductive health and childbirth; 3 Good Health and Well Being; 1114 Paediatrics and Reproductive Medicine; 3215 Reproductive medicine; 4204 Midwifery